CONTENT, SUBJECT AND METHOD OF TEXT ANALYSIS SCIENCE (Лучшие интеллектуальные исследования, 2025)
Abstract: The science of textual analysis is one of the most important areas of linguistics, it is a scientific field aimed at studying the text in depth, determining its internal structure, semantic and communicative properties. Textual analysis studies the content, structure, style, and communicative functions of texts that are the highest units of the language. This science helps to better understand the processes of language and communication, to determine how language tools are used. Textual analysis is important not only in linguistics, but also in many fields, such as literary studies, journalism, translation.